Implementation of Islamic Leadership Values by School Principals in Enhancing Teacher Competence in Public Junior High Schools in Indramayu - Sahrudin, Sahrudin (Eduprof : Islamic Education Journal, 2025)
This study aims to examine the implementation of Islamic leadership values by school principals in improving teacher competence at public junior high schools in Indramayu Regency. Moral and spiritual values such as amanah (trustworthiness), adil (justice), musyawarah (consultation), and uswah hasanah (exemplary conduct) are the main focus in shaping effective educational leadership. A qualitative descriptive approach was employed, with data collected through interviews, observations, and document analysis at SMPN 1 Kandanghaur and SMPN 1 Anjatan.The findings reveal that the consistent application of Islamic leadership values by principals significantly contributes to the enhancement of teacher competencies in pedagogical, professional, personal, and social aspects. Principals who internalize Islamic values are able to foster a conducive school culture, encourage reflective practices, enforce discipline and fairness, and strengthen interpersonal relationships among teachers. As a result, teacher motivation increases, professional development becomes more focused, and instructional quality improves. this study recommends the development of structured leadership training programs based on Islamic values and active collaboration among stakeholders to institutionalize this leadership model in order to improve the quality of education in public schools.